HUBUNGAN PENGALAMAN KERJA DAN PENDIDIKAN DENGAN KUALITAS KINERJA GURU - Julia Ningsih, Alqansa Rahmi Putri, Ica Monika, Miftahir Rizqa; Radhiatul Husni (CV. ADIBA AISHA AMIRA, 2024)
Two major determinants of the caliber of teacher performance are education and work experience. The purpose of this study is to ascertain how work experience, educational background, and the caliber of teaching performance are related to one other. The study's findings demonstrate that a teacher's effectiveness is significantly improved by having a high degree of education and a lot of professional experience. Work ability acts as a mediator between the considerable effects of work experience and educational background on teacher performance. Additionally, work motivation, views of the workplace, and teaching abilities all have a big impact on teachers' effectiveness.Keywords : Administration, Role of Teachers, Education. According to the study's findings, educators with advanced degrees and a wealth of professional experience are better able to instruct students and foster higher performance. This study has applications for creating more efficient curricula and boosting teacher motivation at work, both of which will raise educational standards.